Company Profile sebagai Media Public Relations dalam Pembentukan Citra Positif KompasTV - Nugraheni, Fadila Fitri Eka; Priatna, Wahyu Budi (Jurnal Pustaka Komunikasi, 2026)
This study aims to examine how KompasTV's company profile plays a role in building and strengthening the company's positive image in the eyes of the public and business partners. In today’s fast-paced digital communication era, media companies like KompasTV are required not only to present information accurately and attractively but also to maintain the trust of the public and business partners through effective communication. This study uses a descriptive qualitative method by conducting interviews with the Public Relations staff of KompasTV to gain a deeper understanding of the strategies used in presenting the company profile. The results show that KompasTV’s company profile effectively communicates the company’s identity, core values, vision, mission, and programs in a clear, engaging, and easily understandable way. The company profile functions not merely as a formal document but also as an effective communication tool that helps build trust and enhance the loyalty of both the public and business partners. Therefore, the company profile serves as an essential instrument for supporting organizational communication, shaping a strong corporate image, and maintaining KompasTV’s position as a professional and reliable media organization in the highly competitive media industry.